Tragedy of great power politics - Mearsheimer, John J (New York, 2001)
The terrorist attacks of September 11, 2001, sadly shattered these idyllic illusions, and John Mearsheimer$1 (Bs masterful new book explains why these harmonious visions remain utopian. To Mearsheimer, great power politics are tragic because the anarchy of the international system requires states to seek dominance at one another$1 (Bs expense, dooming even peaceful nations to a relentless power struggle. Mearsheimer illuminates his theory of offensive realism through a sweeping survey of modern great power struggles and reflects on the bleak prospects for peace in Europe and northeast Asia, arguing that the United States$1 (Bs security competition with a rising China will intensify regardless of "engagement" policies.s
Keywords: World politics-19th century